UJI AKTIVITAS PRODUK KECANTIKAN FACIAL WASH TERHADAP BAKTERI PENYEBAB JERAWAT (Propionibacterium acnes) - Harnis, Zola Efa; Harahap, Nina Irmayanti Harahap; Simorangkir, Delisma Simorangkir; Sari, Rika Puspita; Hayati, Silmi Hayati (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2024)
Background: Acne occurs on the surface of the skin of the face, neck, chest, and back when the oil glands in the skin are overactive so that the pores of the skin will be clogged with excessive fat deposits. If the deposits are mixed with sweat, dust, and other dirt, it can cause fat deposits with black spots on them called blackheads. If the blackheads have a bacterial infection, then there is an inflammation known as acne, one of the bacteria is Propionibacterium acnes. Objective: This study aims to test the antibacterial activity of face wash containing gotu kola leaf, moringa leaf, and green tea leaf extracts. Results: Inhibition zone test results obtained facial wash containing gotu kola leaf extract (Facial wash B), moisture test results obtained that facial wash containing green tea leaf extract (Facial wash C) is more effective in moisturizing the skin, brightness test results obtained that facial wash containing moringa leaf extract (Facial wash A) is more effective in brightening the skin.